2017
DOI: 10.4046/trd.2017.80.3.284
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to the Diagnostic Yield of Flexible Bronchoscopy without Guidance in Bronchoscopically Invisible Peripheral Lung Lesions

Abstract: BackgroundWe aimed to analyze the factors predicting the diagnostic performance of flexible bronchoscopy without guidance in peripheral lung lesions that are endoscopically invisible.MethodsThis was a retrospective study conducted in St. Paul's Hospital, The Catholic University of Korea, between January 2007 and March 2013. We included all patients who received bronchoscopy during this period. The analyzed variables were age, sex, the etiology of the lesion, lesion size, distance from the pleura, and presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Using published data 3 , we reviewed only the reported results for the final diagnosis of peripheral lung cancer during non-guided FB up to 2018 (Table 3). Of nine studies, washing was performed together with TBB in five 8,[11][12][13][14] , before TBB or brushing in three 12,13,15 , and after other procedures in two studies 8,11 . The average diagnostic yields of brushing and washing from the literature review were 19.6% (range 12.6-31.4%) and 24.4% (range 5.9-50.9%), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Using published data 3 , we reviewed only the reported results for the final diagnosis of peripheral lung cancer during non-guided FB up to 2018 (Table 3). Of nine studies, washing was performed together with TBB in five 8,[11][12][13][14] , before TBB or brushing in three 12,13,15 , and after other procedures in two studies 8,11 . The average diagnostic yields of brushing and washing from the literature review were 19.6% (range 12.6-31.4%) and 24.4% (range 5.9-50.9%), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Our research suggested that lesion 2cm (p = 0.042) and the bronchial generation of lesion ≤ 5th generation (p = 0.005) could affect the diagnostic yields of HBM-EBUS-TBLB, as shown in the multivariate analysis. Previous studies showed that a bronchus sign on CT [21] , pathology [22,23] , non-upper lobe location, tobacco use and peripheral transbronchial needle aspiration [24] independently correlated with improved diagnostic yield. However, we found that the impact of the diagnosis yield by HBM-EBUS-TBLB was depended on two factors: lesion characters and lesion location.…”
Section: Discussionmentioning
confidence: 97%
“…Both procedures have their own advantages, and FLB has the benefit of avoidance of general anaesthesia, easyto-use instruments, and widespread availability. However, the failure rate of FLB is not negligible, especially when the diagnosis is delayed and in cases of peripherally located FBs [5][6][7]. Difficulty in maintaining airway patency can be a challenge, and complete cooperation of the patient is essential for the procedure.…”
Section: Introductionmentioning
confidence: 99%